Development of a Semielliptical Partial Ground Plane Antenna for RFID and GSM-900. (9th April 2014) - Zaman, M. R.; Azim, R.; Misran, N.; Asillam, M. F.; Islam, T.
Abstract : A novel compact broadband patch antenna for UHF (ultrahigh frequency), RFID (radio frequency identification), and GSM-900 (global system for mobile communications) band is shown in this paper. The antenna is composed of an ellipse shape annular ring at the patch. The ground plane of the planar antenna is modified with a semiellipse shape slot. The structure can generate substantial amount of current at the feed-line. The geometry of the antenna is evaluated by using HFSS simulation software and deliberated across the paper. Parametric study is exhibited to delineate the response change of the antenna. The antenna has a physical width of 0.24 λ and length of 0.3 λ . It covers a frequency starting from 0.9 GHz to 1.08 GHz. A fractional bandwidth of 18.2% has been achieved from 0.9 GHz till 1.08 GHz. An average gain of 5.5 dBi is achieved at the resonance frequency. The simulated and measured results have good agreement.